2011
DOI: 10.1096/fj.10-174904
|View full text |Cite
|
Sign up to set email alerts
|

OxLDL up‐regulates microRNA‐29b, leading to epigenetic modifications of MMP‐2/MMP‐9 genes: a novel mechanism for cardiovascular diseases

Abstract: MicroRNAs (miRNAs), small noncoding RNAs, can control gene expression by binding to their target genes for degradation and/or translational repression. Epigenetic mechanisms are defined as heritable changes in gene expression that do not involve coding sequence modifications. Both mechanisms play an important role in maintaining physiological functions and are also related to disease development. However, few studies report that miRNA-mediated epigenetic regulations are involved in atherosclerosis. In the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
124
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(133 citation statements)
references
References 48 publications
5
124
1
2
Order By: Relevance
“…Various miRNAs have effects on controlling the integrity of vessels and the function of macrophage in every stage of atherosclerosis. The work from Chen's group suggested that miR-29b was up-regulated in vascular smooth muscle cells (VSMCs) with ox-LDL treatment, which might target on MMP2 leading to a reduction of VSMC migration [13]. Lovren and colleagues have shown that overexpressing miR-145 in VSMCs decreased the plaque size of atherosclerosis and favor plaque stability [14].…”
Section: Big Nucleusmentioning
confidence: 99%
“…Various miRNAs have effects on controlling the integrity of vessels and the function of macrophage in every stage of atherosclerosis. The work from Chen's group suggested that miR-29b was up-regulated in vascular smooth muscle cells (VSMCs) with ox-LDL treatment, which might target on MMP2 leading to a reduction of VSMC migration [13]. Lovren and colleagues have shown that overexpressing miR-145 in VSMCs decreased the plaque size of atherosclerosis and favor plaque stability [14].…”
Section: Big Nucleusmentioning
confidence: 99%
“…Additionally, it was shown that oxLDL-induced epigenetic suppression of FOXP3 down-regulated T regulatory cells, subsequently increasing the risk of acute coronary syndrome [260]. OxLDL raised significantly MMP-2/MMP-9-mediated migration of human aortic SMCs by epigenetic effects mediated by miRNA [261].…”
Section: Histone Deacetylasesmentioning
confidence: 99%
“…The miR-29b can also revert the aberrant methylation by targeting the DNA (cytosine-5)-methyltransferase 3a (DNMT3a) and DNMT3b genes (Fabbri et al, 2007). miR-29b plays an important role in oxLDL-mediated methylation of matrix metalloproteinase-2 (MMP-2)/ MMP-9 genes (Chen et al, 2011). (3)At the transcriptional level, the miR-29b cluster is involved in the group of interferon (IFN)-and signal transducers and activators of transcription (STAT)-regulated genes (Schmitt et al, 2012).…”
Section: The Regulation Of Mir-29bmentioning
confidence: 99%